Enabling 1536-Well High-Throughput Cell-Based Screening through the Application of Novel Centrifugal Plate Washing. (July 2017) - Knight, Sinead; Plant, Helen; McWilliams, Lisa; Murray, David; Dixon-Steele, Rebecca; Varghese, Anet; Harper, Paul; Ramne, Anna; McArdle, Paula; Engberg, Susanna; Bennett, Neil; Blackett, Carolyn; et al.
Cell-based assays have long been important within hit discovery paradigms; however, improving the disease relevance of the assay system can positively affect the translation of small-molecule drug discovery, especially if adopted in the initial hit identification assay. Consequently, there is an increasing need for disease-relevant assay systems capable of running at large scale, including the use of induced pluripotent stem cells and donor-derived primary cells. Major hurdles to adopting these assays for high-throughput screening are the cost, availability of cells, and complex protocols. Miniaturization of such assays to 1536-well format is an approach that can reduce costs and increase throughput. Adaptation of these complex cell assays to 1536-well format brings major challenges in liquid handling for high-content assays requiring washing steps and coating of plates. In addition, problematic edge effects and reduced assay quality are frequently encountered. In this study, we describe the novel application of a centrifugal plate washer to facilitate miniaturization of a range of 1536-well cell assays and techniques to reduce edge effects, all of which improved throughput and data quality. Cell assays currently limited in throughput because of cost and complex protocols may be enabled by the techniques presented in this study.